The Influence of Financial Literacy and Financial Inclusion on Investment Decisions in Generation Z in West Java - Lusi Sawitri; Suherman, Acep; Sudarma, Ade (Primanomics : Jurnal Ekonomi & Bisnis, 2024)
In the current modern economic era, public awareness of long-term financial planning is increasing, including in terms of investment. Investment is the desire to utilize some of the existing funds or resources to make a profit in the future. However, when investing, there are still many investors who act irrationally and become victims of illegal investments. Therefore, it is important to understand the factors that influence investment decisions, especially among Generation Z. This study aims to analyze the influence of financial literacy and financial inclusion on investment decisions in Generation Z in West Java. This study uses a quantitative method with primary data collected through questionnaires. The research sample consisted of 146 Generation Z respondents in West Java, selected using the purposive sampling technique. Data analysis uses multiple linear regression using SPSS version 27 software. The results of this study show that partially financial literacy has a significant effect on the investment decisions of generation z in West Java; Financial inclusion has a significant effect on the investment decisions of generation z in West Java. Then simultaneously financial literacy and financial inclusion have a significant effect on the investment decisions of generation z in West Java. The determination coefficient in this study was 36.3% and the remaining 63.7% was influenced by other factors that were not studied in this study.